Application Of Stad Method To Increase Learning Outcomes Themes of Students oClass IV.b 0413 Ampolu State SD Negeri Tp 2020/2021 - Derisna Ningsih Daulay; Nauli Tama Sari (STKIP Rokania Pasir Pangaraian, 2021)
The purpose of this study is to describe the application of the model STAD type cooperative learning in improving student learning outcomes in the eye Thematic lessons for class IV SD Negeri 0413 Ampolu for the 2020/2021 academic year. Technique data collection through observation sheets to determine student learning activities and question sheet to find out student learning outcomes. Data analysis techniques in this study namely by using the formula for improving learning outcomes, the interpretation of the activity scale study. Based on the results of the study, it can be seen that by applying the model STAD cooperative type can improve student learning outcomes in grade IV SD Negeri 0413 Ampolu on thematic material in the first cycle student learning outcomes reached 83% completeness in the second cycle reached 93%. With an average learning outcome of 83.3 to 87.3. From result From the analysis it can be concluded that the application of the STAD-type cooperative learning model can improve student learning outcomes in thematic subjects of class IV School Basic